#TITLE_ALTERNATIVE# - ADELA NIM : 11614002, MONIKA
Ciprofloxacin is a broad spectrum antibiotic that is commonly used by breeders to cure chickens with bacterial disease. Concentration of ciprofloxacin in the poultry products should be under maximum residual limit (MRL) to prevent antimicrobial resistance. Therefore, pharmacokinetics parameters and withdrawal time of ciprofloxacin in the poultry products should be determined. In this research, ten laying hens were given ciprofloxacin by intravenous and oral route of administration. Twelve blood samples from each laying hens were then analysed by using High Performance Liquid Chromatography with UV detector. Ciprofloxacin, both given by intravenous route and oral route follows two-compartement pharmacokinetic model. Pharmacokinetic parameters of ciprofloxacin in intravenous route are as follows: A= 20.686 Ã‚Â± 9.930 Ã‚Âµg/mL, λ1= 8.024 Ã‚Â± 1.947/hour, B= 2.303 Ã‚Â± 0.585 Ã‚Âµg/mL, λ2= 0.087Ã‚Â± 0.038/hour, k12= 6.045Ã‚Â± 2.134 /hour, k21= 1.240Ã‚Â± 0.961/hour, dan kel= 0.8270,564/jam /hour. Pharmacokinetic parameters of ciprofloxacin in oral route are as follows: A= 1.696 Ã‚Â± 1,168 Ã‚Âµg/mL, λ1= 0.244 Ã‚Â± 0.187/hour, B= 1.380 Ã‚Â± 0.653 Ã‚Âµg/mL, λ2= 0.092 Ã‚Â± 0.044/hour, C= 0.938 Ã‚Â± 0.462 Ã‚Âµg/mL, ka= 1.638 Ã‚Â± 1.070/hour, k12 = 0.029 Ã‚Â± 0.042/hour, k21= 0.206 Ã‚Â± 0.124/hour, dan kel= 0.102 Ã‚Â± 0,071 /hour. The calculated withdrawal time (WT) of ciprofloxacin based on Acceptable Daily Intake (ADI) information is 19.81 hours for intravenous route and 52.27 hours for oral route. In addition, the calculated WT of ciprofloxacin based on Maximum Residual Limit (MRL) information is 29.97 hours for intravenous route and 42.2 hours for oral route.